Epidemiology of Hip Fractures in Two Regions of Ukraine - V. V. Povoroznyuk; N. V. Grygorieva; J. A. Kanis; E. V. McCloskey; H. Johansson; S. S. Strafun; M. O. Korzh; V. M. Vaida; F. V. Klymovytsky; V. S. Forosenko; R. O. Vlasenko (Journal of Osteoporosis)
Worldwide, the number of hip fractures, the most important osteoporotic complication in the elderly, continues to increase in line with the ageing of the population. In some countries, however, including the Ukraine, data on the incidence of hip fracture are limited. This article describes the first analysis to characterize the incidence of hip fracture in the Ukrainian population from the age of 40 years. It is based on data from two regional studies, namely, the Vinnitsa city study and the STOP study, which were performed during 1997–2002 and 2011-2012 years, respectively. Hip fracture incidence rates were demonstrated to increase with increasing age. The rates were higher among younger men than women, however, with a female preponderance from the age of 65 years upwards. The incidence of hip fractures in Ukraine is 255.5 per 100,000 for women aged 50 years and older and 197.8 per 100,000 for men of the corresponding age. Overall, the incidence of hip fracture was comparable with data from neighboring countries, such as Poland and Romania. Hip fractures constitute a serious healthcare problem in Ukraine, and changes in healthcare are required to improve the management and long-term care of osteoporosis and its complications.